Zebrafish Models of Photoreceptor Dysfunction and Degeneration - Noel, Nicole C. L. (Biomolecules, 2021)
Zebrafish are an instrumental system for the generation of photoreceptor degeneration models, which can be utilized to determine underlying causes of photoreceptor dysfunction and death, and for the analysis of potential therapeutic compounds, as well as the characterization of regenerative responses. We review the wealth of information from existing zebrafish models of photoreceptor disease, specifically as they relate to currently accepted taxonomic classes of human rod and cone disease. We also highlight that rich, detailed information can be derived from studying photoreceptor development, structure, and function, including behavioural assessments and in vivo imaging of zebrafish. Zebrafish models are available for a diversity of photoreceptor diseases, including cone dystrophies, which are challenging to recapitulate in nocturnal mammalian systems. Newly discovered models of photoreceptor disease and drusenoid deposit formation may not only provide important insights into pathogenesis of disease, but also potential therapeutic approaches. Zebrafish have already shown their use in providing pre-clinical data prior to testing genetic therapies in clinical trials, such as antisense oligonucleotide therapy for Usher syndrome.